Reforming the IMF : back to the drawing board - Akyüz, Yilmaz (UN New YorkUS, 2005)
Discusses and elaborates a number of broad issues that would need to be taken into account in any serious attempt to make the Fund a genuinely multilateral institution with equal rights and obligations for all its members, in practice as well as in theory.